2020
DOI: 10.22435/hsr.v23i1.2622
|View full text |Cite
|
Sign up to set email alerts
|

Disparitas Pembangunan Kesehatan di Indonesia Berdasarkan Indikator Keluarga Sehat Menggunakan Analisis Cluster

Abstract: Healthy Indonesia Program with family approach was the main health development program to support the achievement of Healthy Indonesia Program objectives in the 2015-2019 Ministry of Health strategic plan. There were twelve main indicators to mark the health status of a family. This study aimed at grouping provinces in Indonesia based on Healthy Family Indicators 2018 using cluster analysis. The analysis used secondary data published by Welfare Statistics Indonesia 2018, National Statistics Agency, Republic of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Though the indicators have been an important component in the process of planning and evaluating regional health programs, indicator values have not been evenly distributed across Indonesia. Several studies have found that a regional disparity persists, particularly in the provinces of Papua and West Papua when compared to other provinces in the islands of Java-Bali, Sumatra, Kalimantan, and Sulawesi [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though the indicators have been an important component in the process of planning and evaluating regional health programs, indicator values have not been evenly distributed across Indonesia. Several studies have found that a regional disparity persists, particularly in the provinces of Papua and West Papua when compared to other provinces in the islands of Java-Bali, Sumatra, Kalimantan, and Sulawesi [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Provinces in eastern Indonesia with low-level healthy family indicators are Maluku, North Maluku, West Papua and Papua (cluster 4), while provinces with high-level healthy family indicators (cluster 3) are Riau Islands, Jakarta, Yogyakarta, Bali, East Kalimantan, North Kalimantan, South Sulawesi and Gorontalo. 13 A study on maternal and child health in Papua demonstrated that the e lack for midwives and doctors in Papua is extensive, and there is a very high variation between districts/cities in terms of input and performance. 14 Differences in urban–rural areas, travel time to the hospital and transportation costs predict hospital utilisation among outpatients in Papua.…”
Section: Introductionmentioning
confidence: 99%
“…One of them can be seen from the geographical condition of Maluku Province, which consists of a cluster of islands that poses a challenge to the accessibility of health services in the region. Particular interventions are needed so that health services are felt equally by all Maluku residents (Maryani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%